HUBUNGAN PENGETAHUAN IBU TENTANG GIZI DENGAN STATUS GIZI ANAK BALITA DI PERUMNAS BELIMBING KELURAHAN KURANJI PADANG - FITRI, IZZATI ELSA; Yusuf, Liswarti; Kasmita, Kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
This study aimed to describe the mother's level of knowledge about nutrition , describe the nutritional status of children under five , and maternal knowledge about the relationship of nutrition and nutritional status of children under five in Housing Belimbing.Jenis this research is quantitative descriptive correlational form . The population in this study were mothers of children under five who have poor nutritional status and malnutrition , amounting to 38 orang.Analisis using the Pearson correlation coefficient Product Moment Correlation and continued with the t test for the significance analysis korelasi.Berdasarkan coefficient description of the data analysis results , that percentage the level of achievement of the respondents on the variables of maternal nutrition knowledge was highest in the percentage of 58 % with the low category , nutritional status of children under five variables obtained results from 38 infants who have nutritional problems are 11 % who suffer from malnutrition , and the remaining 89 % are children under five nutritional status less . The results of the correlation analysis suggests that there is a positive and significant relationship between mothers' knowledge of nutrition with nutritional status of children in the Housing Carambola . Â Â Keywords: Mothers' Knowledge OfNutrition, Nutritional Status